Coordination of abscisic acid and hydraulic signals in stomatal closure and yield of soybean genotypes with varying isohydry under different water conditions - Yang, Sanwei; Zhang, Haixia; Jin, Yi; Turner, Neil C.; Pang, Jiayin; Chen, Yinglong; He, Jin (Agricultural water management, 2025)
Understanding soybean responses to drought stress is critical for breeding drought-tolerant varieties. The extent of stomatal regulation of leaf water potential during drought stress can be characterized by the degree of isohydry. We hypothesize that abscisic acid (ABA) and hydraulic signals, two key factors influencing stomatal regulation, coordinate differently to regulate stomatal closure and impact yield performance under varying drought intensities in soybeans with different isohydric behaviors. To test this, we selected four landraces and four modern cultivars exhibiting diverse isohydric behaviors and conducted a progressive drought experiment. The experiment measured stomatal conductance, photosynthetic rate (Pn), and leaf hydraulic conductance (Kleaf) as soil moisture progressively declined. Additionally, a water control experiment assessed foliar ABA content, osmotic adjustment (OA), and yield components under moderate (50 % pot capacity) and severe stress (30 % pot capacity) drought stress were compared relative to well-watered conditions. Results showed that modern cultivars, characterized by more isohydric behavior, produced higher ABA levels, triggering earlier stomatal closure at higher soil water content, which was subsequently modulated by hydraulic signals during prolonged drought. Isohydric genotypes also displayed enhanced OA, enabling them to maintain high Pn under severe drought stress. Under moderate drought stress, the isohydric cultivars experienced greater yield lose (21 % and 25 % for two isohydric cultivars vs. −8 % and 1 % for two landraces) and increased less water use efficiency for grain (WUEg). However, under severe drought stress, isohydric genotypes suffered less yield reduction (70 % and 72 % for isohydric cultivars vs. 79 % and 77 % for two anisohydric landraces) and increased more WUEg compared to anisohydric genotypes. Overall, isohydric genotypes, which exhibit a more conservative water-use strategy, are better suited for regions prone to severe drought stress. In contrast, anisohydric genotypes may perform better in regions with more reliable water availability. •Hydroscape area can represent the degree of isohydry in soybean.•Cultivars produce more ABA, enabling earlier stomatal closure to conserve water.•Cultivars enhanced osmatic adjustment to maintain higher photosynthesis under severe drought.•Modern soybean cultivars exhibit more isohydric traits with less yield reduction compared with landraces.